Task-based defect management: anatomical classification - Almusharraf, Abdullah; Whyte, Andrew (Emerald Group Publishing, 2016)
Purpose – Studies on the construction defects and quality deviations have been commissioned and published in many countries, showing the global status of the issues related with construction defects. Therefore, the quality of the adapted practices in construction projects can be improved if the pattern of the sub-task, specifically the quality deviations and construction defects from the requirements and specifications is identified and understood. The purpose of this paper is to improve understanding of the behavior and pattern of the more sensitivity sub-task requirements (STRs) through the anatomy process of a particular task. Design/methodology/approach – Six criteria have been classified for the levels of the estimated STRs quality deviations. The proposed study classifications were examined through the 3,030 cases of 17 STRs from compression concrete members (i.e. column). Findings – Most of the STRs were found to be prone to deviations and the sensitivities of the STRs toward deviations and defects are varied across all STRs. The study reveals that three of the 17 STRs were observed as perfect works, ten STRs as acceptable works and four STRs as defective works. Originality/value – The study found that the sub-task deviation patterns cannot be generalized and must be individually studied to recommend the appropriate proactive measures.